The Effect of Trump’s Economic Policies on the US Economy - MENNAI, SADANI, Assil Abdessamed (University of El-oued, 2022)
أصبحت السياسات الاقتصادية للولايات المتحدة قضية متنازع عليها بشدة فيما يتعلق بالإمكانيات والصعوبات التي تواجه ا لاقتصاد الأمريكي. عندما تولى ترامب منصبه ، أصبح تأثير هذه الإجراءات موضوعًا مثيرًا للجدل بشكل خاص. الغرض من هذا البحث هو دراسة تأثير السياسات الاقتصادية لإدارة ترامب على الاقتصاد الأمريكي. لتحقيق هذا الغرض ، تم استخدام نهج وصفي للتحقيق في كيفية تأثير هذه السياسات على الاقتصاد الأمريكي في جميع أنحاء إدارته. تضمن ت البيانات التي تم جمعها لهذه الدراسة ولكنها اقتصرت على الخبراء الذين يتعاملون مع الموضوع والتقارير التي ناقشت الموضوع. تم تحليل هذه النتائج وتم الحصول على العديد من النتائج. وكشفت النتائج أن السياسات الاقتصادية التي تنفذها إدارة ترامب أثرت سلبا على اقتصا د الولايات المتحدة. ومن النتائج المهمة الأخرى أن هذا الضرر قد حدث على مستوى الهيمنة الدولية بسبب قرار ترامب المتهور بالانسحاب من الاتفاقيات الدولية مثل الشراكة عبر المحيط الهادئ. وضع الأخير التنافس مع الولايات المتحدة. الصين ، في وضع أفضل للسيطرة على The economic policies of the United States have become a highly contested issue concerning the possibilities and difficulties facing the American economy. When Trump took office, the effect of these measures became a particularly contentious topic. This research aims to examine the impact of the Trump administration's economic policies on the U.S. economy. To achieve this purpose, a descriptive approach was employed to investigate how these policies affected the U.S. economy throughout his administration. The data gathered for this study included but were limited to the experts' take on the topic and the reports that discussed theissuec. These were analysed, and several findings were generated. The results revealed that the economic policies implemented by Trump's administration negatively affected the economy of the United States. Another significant finding was that this harm was done at the level of international domination due to Trump's reckless decision to withdraw from international agreements such as the Trans-Pacific Partnership. The latter put the U.S.'s rivalry, with China, in a better position to take control of the world's economy.
Keywords: عصر ترامب ، السياسات الاقتصادية ، الاقتصاد الأمريك ي .; Trump era, Economic Policies, U.S. economy.